Material Vigilance and Proper Use of Implantable Medical Devices: Tracking the Traceability of Dental Implants in Healthcare Institutions - DAOUDI, Hajar; CHOKHMANE, Wafaa; JAMAI-NAFIA, Hanane; EL HARTI, Jaouad; AIT EL CADI, Mina (Jour Med Resh and Health Sci, 2023)
Introduction: Material vigilance is implemented to ensure the safety of patients and users of medical devices. The traceability of dental implants (MDIs) is regulated and must meet various healthcare, financial, and proper use objectives. The goal is to assess the traceability of implants in healthcare facilities and evaluate the practices of professionals regarding this activity to ensure the proper use of MDIs. Materials & Methods: An investigation was conducted in 26 public and private institutions using an open questionnaire. The questionnaire included information on dental implant traceability at the internal pharmacy (PUI), surgical odontology service, patient medical records, and information provided to the patient. The questionnaire was made available online using Google Forms to automatically collect the results. The data were analyzed using Jamovi 2.3.18, and the results are presented in percentages and averages. Results & Discussions: A total of 60 responses were obtained, including 15 (25%) from public healthcare institutions, 32 (53.4%) from dental clinics, and 13 (21.6%) from private healthcare institutions. It was observed that dental implant identification is almost exhaustive, with a traceability percentage of 87% at the PUI. 85% of dentists use computer software, and 5% use a sharing tool with the PUI. 94% of dentists maintain patient records, while 6% of implanted MDIs do not have traceability. 65% of healthcare professionals confirmed that they provide documents to patients, while 35% do not provide patient records. This study demonstrates the importance of computerizing the MDI circuit. The use of software to record and preserve all health and financial traceability information, as well as the acquisition of automatic barcode readers, is now a prerequisite for implementing traceability in healthcare facilities. Traceability ensures the quality and safety of implantable medical devices, enables prompt detection of issues, and facilitates necessary corrective measures. Conclusion: The traceability of dental implants is a significant public health issue. Material vigilance and traceability are two essential elements for ensuring the safety and quality of implantable medical devices. Manufacturers and regulatory authorities are working together to establish effective surveillance and traceability systems to guarantee the safety of patients and users of medical devices.